Desain Stack Cabinet Multifungsi Sebagai Solusi Keterbatasan Ruang pada Hunian Rumah Susun - Kunthi Lathifatus Syarifah; Mochamad Junaidi Hidayat (SPACEPRO: Product Design Jurnal, 2026)
This study aims to design a multifunctional stack cabinet for residents of low-cost flats (rumah susun) in Surabaya as a solution to limited storage space and restricted access for transporting large furniture. Observations and interviews were conducted directly at two locations: RUSUNAWA Pesapen and RUSUN Menanggal, Surabaya. A mixed method approach was applied, combining qualitative methods through field observation, in-depth interviews, and documentation, with quantitative methods through a Voice of Customer (VOC) questionnaire involving 15 residents. Design analysis was carried out across eight dimensions: needs, materials, systematics, placement, color, anthropometry, form, and ergonomics. The results indicate that residents primarily need storage in the form of a wardrobe, TV cabinet, shoe rack, and display rack. The final design applies the Minimalist Stacking concept with a Scandinavian style, using a combination of plywood and particle board materials with HPL and decosheet finishing in a monochromatic white, black, and natural wood palette. The stacking system allows vertical arrangement to maximize space efficiency, making it suitable for the limited interior conditions of low-cost flats.